Facile one-pot synthesis of self-assembled nitrogen-doped carbon dots/cellulose nanofibril hydrogel with enhanced fluorescence and mechanical properties. Issue 10 (7th May 2020) - Chen, Xueqi; Song, Zihui; Li, Shaopeng; Tat Thang, Nguyen; Gao, Xing; Gong, Xinchao; Guo, Minghui
Abstract : A facile one-pot method is used to synthesize and self-assemble nanofibril cellulose hydrogels with carbon dots as intensity enhancement and fluorescent emission factors. Abstract : The preparation and functionalization of biomass-based hydrogels that can be used in the field of biomedicine have received an increasing amount of attention. Carbon dots are a kind of fluorescent carbon nanomaterial with stable fluorescence emission and low biotoxicity, therefore the introduction of carbon dots into the biomass-based hydrogel can make it have a broader application prospect. In this work, fluorescent nitrogen-doped carbon dots/cellulose nanofibril composite hydrogel (NCDs/CNF-gel) with exceptional mechanical properties was successfully fabricated by a facile one-pot green hydrothermal treatment. The properties of NCDs/CNF-gel prepared at different temperatures and CNF concentrations were investigated by electron microscopy, Fourier-transform infrared spectroscopy, X-ray diffraction, fluorescence spectroscopy, rheology, and mechanical tests. NCDs/CNF-gel with injectable, pressure-resistance and excellent fluorescence properties can be obtained by controlling the hydrothermal treatment temperature. Furthermore, the self-assembly mechanism of NCDs in the hydrogel network and the improvement mechanism of hydrogel compressive strength were explored. The NCDs/CNF-gel exhibited acid-resistant and alkaline sensitive blue-green fluorescent emission. The outstanding biocompatibility, excellent fluorescence and mechanical properties of NCDs/CNF-gels, and their facile fabrication render these so-prepared gels promising candidates for future biomedical applications.